ANALISIS STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA GUNA MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KPPBC BENGKULU - Putri, Anggun Desmayna; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Kantor KPPBC bengkulu is a company that pays great attention to its human resources, but the improvement of human resources in improving employee performance is still not optimal so a strategy is needed to overcome these problems. This study aims to identify internal and external factors regarding improving human resources in improving employee performance and formulating strategies for improving human resources in improving employee performance. The research method used is SWOT analysis.The results of this study can be concluded that the results of the IFAS matrix calculation, namely the weighted score for strength factors, amounted to 2.21 overall IFAS with an average score of 4.17, indicating that strength factors are stronger than weakness factors. The results of the EFAS matrix calculation, namely the weighted score for the opportunity factor, amounted to 1.96. and the overall result of EFAS with an average score of 0.92 shows that the opportunity factor is stronger than the threat factor.The results of the SWOT analysis of human resource development strategies to increase employee productivity carried out are strength-opportunity strategies because they have a combined SWOT strategy value (4.17) higher than the weakness- Opportunity strategy (2.8), strength-threat strategy (3.13) maupurn weakness-threat strategy (1.76).Human resource development strategies to improve work culture, job training, leadership training, communication and career paths for employees are carried out, namely providing training or internships, increasing salaries and decent awards for productive employees. Keywords: HR Improvement Strategy, EFE Matrix, IFE Matrix, SWOT Matrix,